Pengembangan Aplikasi Bengkel Las di Kediri dengan Metode Extreme Programming - Lisdiyanto, Angga; Nugroho, Rizky Aditya; Andhyka, Awang; Wibowo, Agus; Winarti, Winarti; Budiman, Budiman (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
In the ever-evolving software development industry, efficient methodologies are crucial for delivering high-quality applications on time. Extreme Programming (XP) is one of the methodologies adopted for various types of software projects, offering flexibility and responsiveness to user feedback. This study aims to apply the XP method in the development of an online welding workshop mobile application and document the process and results. The main goal is to explore how XP practices contribute to the development of a functional mobile application and provide valuable insights for future application development strategies. The XP method was applied over a seven-week period, focusing on small iteration planning (small releases), Test-Driven Development (TDD), and Continuous Integration (CI). These techniques were employed to ensure efficient development, continuous testing, and close collaboration with users to meet their needs. The application of XP in this project demonstrated its effectiveness in delivering a functional, user-focused mobile application in a short timeframe. This study documents the entire XP process and can serve as a reference for future development strategies, particularly in mobile and web app development.